Desain Dashboard Business Intelligence untuk Monitoring Kinerja Operasional Freight Forwarding Menggunakan Power BI - Vanness Matthew Tjoeng; Darius Andana Haris; Meirista Wulandari (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
This study aims to design a Business Intelligence dashboard to support operational performance monitoring in Freight Forwarding Project Cargo services at PT XYZ. The company currently relies on manual reporting processes by exporting operational data from SAP and Microsoft SharePoint into spreadsheet files, resulting in inefficiencies and difficulties in monitoring shipment activities. This research adopts the Data Warehouse Lifecycle methodology using The Nine Steps of Kimball approach. Operational data obtained from SAP and Microsoft SharePoint were processed through the Extract, Transform, Load (ETL) stages using Power Query and visualized using Microsoft Power BI Desktop. The resulting dashboard provides key performance indicators (KPIs), including Total Shipment, Delayed Shipment, Average Lead Time, Average Delay Time, and On-Time Shipment Percentage, along with supporting visualizations for operational analysis. The implementation results indicate that the dashboard is capable of integrating operational data into a centralized platform and presenting information interactively to support monitoring activities and operational decision-making. The developed dashboard is expected to improve reporting efficiency, enhance visibility of shipment performance, and support data-driven decision-making within the company.